The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/s0033291715001221
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genetic risk for emotional eating across the menstrual cycle: a longitudinal study

Abstract: Background Previous studies show significant within-person changes in binge eating and emotional eating across the menstrual cycle, with substantial increases in both phenotypes during post-ovulation. Increases in both estradiol and progesterone levels appear to account for these changes in phenotypic risk, possibly via increases in genetic effects. However, to date, no study has examined changes in genetic risk for binge phenotypes (or any other phenotype) across the menstrual cycle. The goal of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 55 publications
5
38
0
Order By: Relevance
“…Our findings preliminarily confirm hypotheses put forth in our previous paper (Klump et al, 2015) about the potential effects of ovarian hormones on etiologic risk. That study examined changes in heritability across the menstrual cycle and showed substantial shared environmental (and minimal genetic) influences on emotional eating during pre-ovulation, and significant genetic (and minimal shared environmental) influences in post-ovulation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings preliminarily confirm hypotheses put forth in our previous paper (Klump et al, 2015) about the potential effects of ovarian hormones on etiologic risk. That study examined changes in heritability across the menstrual cycle and showed substantial shared environmental (and minimal genetic) influences on emotional eating during pre-ovulation, and significant genetic (and minimal shared environmental) influences in post-ovulation.…”
Section: Discussionsupporting
confidence: 91%
“…Nonshared environmental effects were found to be important in low and high groups for both hormones, with decreasing effects when moving from low to high hormone groups. These results mimic what we observed in our menstrual cycle study where nonshared environmental factors were present across all phases of the cycle, yet they decreased somewhat when moving from pre- to post-ovulation (Klump et al, 2015). …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations